2013
DOI: 10.4067/s0718-95162013005000012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of arbuscular mycorrhiza inoculation on plant growth, biological and physiological parameters and mineral nutrition in pepper grown under different salinity and p levels

Abstract: A study was conducted in a greenhouse, to investigate the effects of arbuscular mycorrhizal fungi (Glomus intraradices), soil salinity and P availability on growth (leaf area and dry weight), nutrient absorption and ion leakage, chlorophyll, soluble sugar and proline content and alkaline phosphatase activity of pepper plants (Capsicum annuum L.). Plants were grown at four levels of salinity (0, 50, 100 and 200 mM NaCl) and two P levels (10 and 40 mg kg -1). Colonisation was 80% to 51% in non-stressed and high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
76
0
11

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(102 citation statements)
references
References 34 publications
15
76
0
11
Order By: Relevance
“…The AM fungi root colonization in green pepper was reduced by salinity stress regardless of AM fungi inoculation status (Table 2). These findings are in agreement with other researchers working on different vegetable crops, who reported that salinity not only affects the host plant growth but also the AM fungi colonization [2,[6][7][8]. Salinity can reduce AM colonization capacity, spore germination and inhibiting growth of hyphae of the fungus [12,22,23].…”
Section: Mycorrhizal Colonizationsupporting
confidence: 82%
See 2 more Smart Citations
“…The AM fungi root colonization in green pepper was reduced by salinity stress regardless of AM fungi inoculation status (Table 2). These findings are in agreement with other researchers working on different vegetable crops, who reported that salinity not only affects the host plant growth but also the AM fungi colonization [2,[6][7][8]. Salinity can reduce AM colonization capacity, spore germination and inhibiting growth of hyphae of the fungus [12,22,23].…”
Section: Mycorrhizal Colonizationsupporting
confidence: 82%
“…Many studies have indicated that AM fungi contribute to plant growth via enhancement of mineral nutrient uptake particularly that of P and N and hence improve salt tolerance in different vegetable crops grown under saline conditions [2,12,[25][26][27][28][29]. Mycorrhizal inoculation has been also reported to reduce the negative effects of Na by maintaining vacuolar membrane integrity, which prevents this ion from interfering in growth metabolic pathways [31].…”
Section: Fruit Yieldmentioning
confidence: 99%
See 1 more Smart Citation
“…Beltrano et al (2013) reported the positive effect of inoculation using arbuscular mycorrhizae fungi (Glomus intraradices) on the growth and functioning of physiological parameters and the absorption of mineral nutrition in bell-pepper (Capsicum annuum L.) plants under different salinity and phosphorus levels, which alleviated the damage caused by salt stress. Moreover, a study by Borie and Rubio (1999) reported an increased tolerance to the presence of phytotoxic aluminum, as well as improved absorption of nutrients such as calcium, magnesium and phosphorus in barley plants (Hordeum vulgare L.) grown in acidic volcanic soils (Borie and Rubio, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few years, many methods have been tested to overcome adverse effects of salinity stress on plants, namely mycorrhiza inoculation (Beltrano et al, 2013) hydrogen sulfide priming (Christou et al, 2013), ABA application (Osakabe et al, 2014) and salicylic acid treatment (LI et al, 2014). Previously, Ashraf et al (2002) reported the combining effects of gibberellic acid and salt stress on the photosynthetic capacity of wheat plants.…”
Section: Introductionmentioning
confidence: 99%